Pengembangan Aplikasi Ujian Online Berbasis Web Dengan Memanfaatkan Teknologi Web Real-Time Communication (WebRTC) Di SMP PGRI BAYAH - Samsul Fauzi; Darmawati (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Exams are a way to measure each student on a material or field of study that has been taught by teachers at school, so that with the results of these measurements, a grade will be obtained that can be used to make various decisions. In the examination process at the PGRI BAYAH Junior High School, it still uses conventional methods, and the assessment process is also still carried out manually by each teacher. Moreover, when the covid19 virus hit the Country of Indonesia as well as other countries in the world so that the Indonesian government at that time required every teaching and learning activity to be carried out remotely or online. Thus, this is a problem for the PGRI BAYAH Junior High School in carrying out teaching and learning activities as well as exams. From this problem, the idea of creating a web-based application by utilizing WebRTC (Web Real-Time Communications) technology in which can carry out the exam process online and can be supervised directly by the exam process by the invigilator and the exam assessment process can be carried out automatically by the system. The method used in the development of this application is the waterfall method. The programming language is javascript. The tools used are, the frontend uses ReactJs, the backend uses ExpressJs, the database uses MySQL and realtime communication using WebRTC. The expected result of making this application is so that PGRI BAYAH Junior High School schools can carry out exams online and can be supervised directly by the exam supervisor, as well as the exam assessment process can be carried out automatically by the system.